Classification Strategies from the End of the Ramesside Period until the Late Period: a Living System - Chantrain, Gaelle (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
This study is part of a diptych. It is conceived as a general theoretical introduction to a forthcoming substantial case study describing the economy of the classifiers system in the Late Period tomb of Menekhibnekau in Abusir. In the first part of the present paper, I shall first go through an overview of the functioning of the classifier system and some suggestions about its evolutive dynamics in diachrony. In the second part, I will introduce five classification strategies that can be encountered in the texts from the end of the Ramesside period down to the Late Period. These strategies will be explained and illustrated by means of two case studies: the manuscript L of the Teaching of Amenemope and the texts from the tomb of Menekhibnekau.